Coverage of Forced Migration in Nigeria: A Content Analysis of Three National newspapers: Coverage of Forced Migration in Nigerian Dailies - OKPOKO, CHINWE; OKORONKWO, MOSES; UCHE OKPOKO, PAT; Catherine Okpoko, Chinwe (International Journal of Psychosocial Rehabilitation, 2024)
Forced migration has become a subject of serious concern in global discourses includingNigeria. An estimated over two million people have sought safe havens in Internally DisplacedPersons (IDPs) camps located in parts of Nigeria, following the increased social dislocationengendered by Boko-Haram insurgency, Fulani herdsmen attacks, communal and ethnoreligious clashes, disputes over land, boundary conflicts between indigenous people and settlers,natural disasters and environmental factors. Content analysis was used to examine reports onforced migration in three Nigerian newspapers, namely, Daily Sun, The Guardian and TheNation, using the agenda setting theory. Constructed week sample of articles published over an  11-month period in 2018 was utilized to arrive at the sample size. Results show that the volumeof coverage on forced migration issues is low, unillustrated and negatively slanted. Conflictsconstituted the main object of attention. It is recommended that Nigerian newspapers should setproper agenda by giving prominence to issues of forced migration and also cover all sides to theissue, including migrant voices and perspectives. What is new about this study is its effort to playup migrant voices and engage in interpretative journalism, in contradistinction to the usualreportage of negative happenstances.